The Effectiveness of Acceptance and Commitment Therapy Counseling and Mindfulness-based Cognitive Counseling to Reduce School Burnout - Susanti, Putri Dwi; Mungin Eddy Wibowo, Mungin Eddy Wibowo; Mulawarman, Mulawarman (Jurnal Bimbingan Konseling)
This study aimed to analyze acceptance and commitment therapy counseling and mindfulness-based cognitive therapy counseling to reduce students? school burnout. To do so, the study employed pretest and multiple posttest design by involving 10 students chosen using purposive sampling from 430 students in Public Senior High School 3 Pati (SMA N 3 Pati). Their data were collected using School Burnout Inventory. Further, the results of repeated measure anova showed that acceptance and commitment therapy and mindfulness-based cognitive therapy counseling were effective to reduce students? school burnout. For more, the discussion in this paper has more focus on the implication of counseling in school practice.